The Economic Drivers of Human Trafficking: Micro-Evidence from Five Eastern European Countries.. - Omar Mahmoud, Toman
Human trafficking is a humanitarian problem of global scale, but quantitative research on the issue barely exists. This paper is a first attempt to explore the economic drivers of human trafficking and migrant exploitation using micro data. We argue that migration pressure combined with informal migration patterns and incomplete information are the key determinants of human trafficking. To test our argument, we use a unique new dataset of 5513 households from Belarus, Bulgaria, Moldova, Romania, and Ukraine. The main result is in line with our expectations: Migrant families in high-migration areas and with larger migrant networks are much more likely to have a trafficked victim among their members. Our results also indicate that illegal migration increases trafficking risks and that awareness campaigns and a reduction of information asymmetries might be an effective strategy to reduce the crime.Human Trafficking; Migrant Exploitation; Illegal Migration; Migration Networks; Eastern Europe;